Treatment of landfill leachate RO concentration by Iron–carbon micro–electrolysis (ICME) coupled with H2O2 with emphasis on convex optimization method. Issue 1 (1st January 2019) - Song, Jianyang; Li, Weicheng; Li, Yuyou; Mosa, Ahmed; Wang, Hongyu; Jin, Yong
ABSTRACT: A combined technology between Iron-carbon micro-electrolysis (ICME) and H2 O2 using scrap iron and granular active carbon was extensively investigated and optimized (three main independent parameters chosen) for chemical oxygen demand (COD) removal of landfill leachate reverse osmosis (RO) concentration by batch experiments. A regression quadratic equation was developed to model the outcome using central composite design (CCD) coupled with response surface methodology. A global optimization method– the convex optimization was applied to determine the optimal parameters. Under optimal parameters determined as C/Fe (Surface area) of 717143.8, H2 O2 concentration of 1687.6 mg/L and pH of 3.8, the corresponding COD removal efficiency was up to 86.9%. Consequently, the COD in the effluent was less than 300 mg/L. The treated water can meet the level B standards of Wastewater Quality Standards for Discharge to Municipal Sewers (CJ 343—2010).